EMMSAD 2011 - Halpin, Terry; Krogstie, John; Proper, Erik (Springer Heidelberg Dordrecht London New York, 2011)
The field of information systems analysis and design includes numerous information modeling methods and notations (e.g., ER, ORM, UML, DFDs, BPMN) that are typically evolving. Even with some attempts toward standardization (e.g., UML for object-oriented design), new modeling methods are constantly being introduced, many of which differ only marginally from existing approaches. These ongoing changes significantly impact the way information systems are analyzed and designed in practice. This workshop focuses on exploring, evaluating, and enhancing current information modeling methods and methodologies. Though the need for such studies is well recognized, there is a paucity of such research in the literature.